Vital post-secular perspectives on Chinese philosophical issues - Pfister, Lauren F. (Lexington Books, 2020)
This book presents a number of contemporary philosophical issues from a wide range of Chinese philosophical texts, figures, and sub-traditions that are usually not addressed in English studies of Chinese philosophical traditions.